Environmental impact indicators for the electricity mix and network development planning towards 2050 – A POLES and EUTGRID model. (15th November 2018) - Louis, Jean-Nicolas; Allard, Stéphane; Debusschere, Vincent; Mima, Silvana; Tran-Quoc, Tuan; Hadjsaid, Nouredine
Abstract: Most prospective studies of the European power system rely on least-cost evaluations. This study assessed the influence of environmental impact indicators on prioritisation of 'dispatchable' technologies in the European energy mix up to 2050, compared with a purely cost-optimal system based on carbon tax incentives, without suppressing economic growth considerations. A model that combined the Prospective Outlook for Long-term Energy Systems model (POLES) and the European and Transmission Grid Investment and Dispatch model (EUTGRID)was used in the analysis. Combined current and prospective life cycle assessment (LCA) methodologies were added to the EUTGRID model to include environmental considerations in the decision-making process. Shifting from an economic to an environmental merit order in prioritisation increased the share of renewables by 2.65% (with variations between countries) and decreased overall emissions by 9.00%. This involved a change in grid infrastructure. Investments were found to be more important when optimisation was based on an environmental criterion on new high-voltage AC power lines, which resulted in a 1.50% increase in the overall cost of the power system. Finally, considering an environmental, instead of an economic, merit order allowed decarbonisation to be achieved slightly faster, resulting in lower cumulative greenhouse gas emissions to the atmosphere. Highlights: Transmission grid and dispatch model using life cycle assessment indicators. Shifting from a cost to an environmental optimisation decreased emissions by 9%. Environmental optimization increased the RES share by +2.65% by 2050. Total power infrastructure investments increased by +1.50%.